2010
DOI: 10.1142/s0219024910005966
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk and Incomplete Information: Filtering and Em Parameter Estimation

Abstract: We consider a reduced-form credit risk model where default intensities and interest rate are functions of a not fully observable Markovian factor process, thereby introducing an information-driven default contagion effect among defaults of different issuers. We determine arbitrage-free prices of OTC products coherently with information from the financial market, in particular yields and credit spreads and this can be accomplished via a filtering approach coupled with an EM-algorithm for parameter estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…The process Y can include macro-economic covariates describing the state of the economy as well as firmspecific and latent variables, as considered e.g. in [19,20]. Let us define the process L = (L t ) 0≤t≤T by L t := logS t and the…”
Section: The Modeling Frameworkmentioning
confidence: 99%
“…The process Y can include macro-economic covariates describing the state of the economy as well as firmspecific and latent variables, as considered e.g. in [19,20]. Let us define the process L = (L t ) 0≤t≤T by L t := logS t and the…”
Section: The Modeling Frameworkmentioning
confidence: 99%
“…It is clear that P D m (t, T ) and F (t, T ) are by construction coherent with the observed default-free and defaultable term structures and also with the rating-based information, due to the definition of Y t . Furthermore, since r t is assumed to be (Y t ) t -adapted, it can be easily shown that (10b) defines an arbitrage-free price system in the investors' filtration (Y t ) t (see [14], Lemma 6).…”
Section: The Filtering Frameworkmentioning
confidence: 99%
“…We aim at extending the modeling approach originally proposed in [14], in order to cover not only applications to pricing but also to risk management. This raises the need to formulate the model under both the physical and the risk-neutral probability measures, which are linked via the risk premium process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations